Hidden decomposers: Revisiting saprotrophy among soil protists and its potential impact on carbon cycling - François Maillard; Fredrik Klinghammer; Vincent E.J. Jassey; Bowen Zhang; Peter G. Kennedy; Enrique Lara; Stefan Geisen; Lars Tranvik; Edith Hammer; Anders Tunlid (Soil Biology and Biochemistry, 2025)

Seasonally variable interactions between dissolved organic matter and mineral particles in an agricultural river - Marloes Groeneveld; Dolly N. Kothawala; Lars J. Tranvik (Aquatic Sciences, 2023)
Streams and rivers form an important link in the global carbon cycle by transporting and transforming large amounts of carbon imported from terrestrial ecosystems to the oceans. Since streams in agricultural areas often experience increased concentrations of suspended mineral particles from soil erosion, they are important sites where dissolved organic carbon (DOC) may be adsorbed to particles and retained in the sediment. As the extent of adsorption varies with the molecular composition of dissolved organic matter (DOM), which is seasonally variable, we expect also the fraction of organic material that adsorbs to mineral particles to fluctuate over time. We sampled the agriculturally impacted River Fyrisån (Sweden) monthly during 1 year, and measured DOC concentration and DOM composition based on several optical properties. At each sampling occasion, we estimated the potential for adsorption by exposing the samples to a reference clay. The potential for adsorption was greatest when riverine DOM had the most terrestrial character, as this fraction of the DOM pool was selectively adsorbed to clay surfaces. The extent of adsorption was negatively related to the concentration of base cations, most notably calcium. We suggest that the observed relationships between the potential for adsorption, DOM composition and base cations are linked by discharge. A bioavailability test at one sampling occasion suggested that DOM remaining after exposure to clay particles was more biodegradable. This implies that adsorption may alter the degradation potential of DOM remaining in solution, which could have far reaching effects on the fate of organic carbon.

Global increase in methane production under future warming of lake bottom waters - Joachim Jansen; Richard Iestyn Woolway; Benjamin M. Kraemer; Clément Albergel; David Bastviken; Gesa A. Weyhenmeyer; Rafael Marcé; Sapna Sharma; Sebastian Sobek; Lars J. Tranvik; Marjorie Perroud; Malgorzata Golub; et al. (Global Change Biology, 2022)
Lakes are significant emitters of methane to the atmosphere, and thus are important components of the global methane budget. Methane is typically produced in lake sediments, with the rate of methane production being strongly temperature dependent. Local and regional studies highlight the risk of increasing methane production under future climate change, but a global estimate is not currently available. Here, we project changes in global lake bottom temperatures and sediment methane production rates from 1901 to 2099. By the end of the 21st century, lake bottom temperatures are projected to increase globally, by an average of 0.86–2.60°C under Representative Concentration Pathways (RCPs) 2.6–8.5, with greater warming projected at lower latitudes. This future warming of bottom waters will likely result in an increase in methane production rates of 13%–40% by the end of the century, with many low‐latitude lakes experiencing an increase of up to 17 times the historical (1970–1999) global average under RCP 8.5. The projected increase in methane production will likely lead to higher emissions from lakes, although the exact magnitude of the emission increase requires more detailed regional studies.

Spatial and vertical distribution of aerobic and anaerobic dark inorganic carbon fixation in coastal tropical lake sediments - Ana Lucia Santoro; Alex Enrich-Prast; David Bastviken; Lars Tranvik; Camila Negrão Signori (Aquatic Sciences, 2021)

Acidification of inland waters - Lars J. Tranvik (Ambio, 2021)

Character and environmental lability of cyanobacteria‐derived dissolved organic matter - Claudia Patriarca; Vicente T. Sedano‐Núñez; Sarahi L. Garcia; Jonas Bergquist; Stefan Bertilsson; Per J. R. Sjöberg; Lars J. Tranvik; Jeffrey A. Hawkes (Limnology and Oceanography, 2021)
Autotrophic dissolved organic matter (DOM) is central to the carbon biogeochemistry of aquatic systems, and the full complexity of autotrophic DOM has not been extensively studied, particularly by high‐resolution mass spectrometry (HRMS). Terrestrial DOM tends to dominate HRMS studies in freshwaters due to the propensity of such compounds to ionize by negative mode electrospray, and possibly also because ionizable DOM produced by autotrophy is decreased to low steady‐state concentrations by heterotrophic bacteria. In this study, we investigated the character of DOM produced by the widespread cyanobacteria Microcystis aeruginosa using high‐pressure liquid chromatography—electrospray ionization—high‐resolution mass spectrometry. M. aeruginosa produced thousands of detectable compounds in axenic culture. These compounds were chromatographically resolved and the majority were assigned to aliphatic formulas with a broad polarity range. We found that the DOM produced by M. aeruginosa was highly susceptible to removal by heterotrophic freshwater bacteria, supporting the hypothesis that this autotroph‐derived organic material is highly labile and accordingly only seen at low concentrations in natural settings.

The CO 2 ‐equivalent balance of freshwater ecosystems is non‐linearly related to productivity - Charlotte Grasset; Sebastian Sobek; Kristin Scharnweber; Simone Moras; Holger Villwock; Sara Andersson; Carolin Hiller; Anna C. Nydahl; Fernando Chaguaceda; William Colom; Lars J. Tranvik (Global Change Biology, 2020)
Eutrophication of fresh waters results in increased CO 2 uptake by primary production, but at the same time increased emissions of CH 4 to the atmosphere. Given the contrasting effects of CO 2 uptake and CH 4 release, the net effect of eutrophication on the CO 2 ‐equivalent balance of fresh waters is not clear. We measured carbon fluxes (CO 2 and CH 4 diffusion, CH 4 ebullition) and CH 4 oxidation in 20 freshwater mesocosms with 10 different nutrient concentrations (total phosphorus range: mesotrophic 39 µg/L until hypereutrophic 939 µg/L) and planktivorous fish in half of them. We found that the CO 2 ‐equivalent balance had a U‐shaped relationship with productivity, up to a threshold in hypereutrophic systems. CO 2 ‐equivalent sinks were confined to a narrow range of net ecosystem production (NEP) between 5 and 19 mmol O 2 m −3 day −1 . Our findings indicate that eutrophication can shift fresh waters from sources to sinks of CO 2 ‐equivalents due to enhanced CO 2 uptake, but continued eutrophication enhances CH 4 emission and transforms freshwater ecosystems to net sources of CO 2 ‐equivalents to the atmosphere. Nutrient enrichment but also planktivorous fish presence increased productivity, thereby regulating the resulting CO 2 ‐equivalent balance. Increasing planktivorous fish abundance, often concomitant with eutrophication, will consequently likely affect the CO 2 ‐equivalent balance of fresh waters.

Potential terrestrial influence on transparent exopolymer particle concentrations in boreal freshwaters - Katrin Attermeyer; Sara Andersson; Núria Catalán; Karolina Einarsdottir; Marloes Groeneveld; Anna J. Székely; Lars J. Tranvik (Limnology and Oceanography, 2019)
Transparent exopolymer particles (TEP) are ubiquitous in aquatic ecosystems and contribute, for example, to sedimentation of organic matter in oceans and freshwaters. Earlier studies indicate that the formation of TEP is related to the in situ activity of phytoplankton or bacteria. However, terrestrial sources of TEP and TEP precursors are usually not considered. We investigated TEP concentration and its driving factors in boreal freshwaters, hypothesizing that TEP and TEP precursors can enter freshwaters via terrestrial inputs. In a field survey, we measured TEP concentrations and other environmental factors across 30 aquatic ecosystems in Sweden. In a mesocosm experiment, we further investigated TEP dynamics over time after manipulating terrestrial organic matter input and light conditions. The TEP concentrations in boreal freshwaters ranged from 83 to 4940 μ g Gum Xanthan equivalent L −1 , which is comparable to other studies in freshwaters. The carbon fraction in TEP in the sampled boreal freshwaters is much higher than the phytoplanktonic carbon, in contrast to previous studies in northern temperate and Mediterranean regions. Boreal TEP concentrations were mostly related to particulate organic carbon, dissolved organic carbon, and optical indices of terrestrial influence but less influenced by bacterial abundance, bacterial production, and chlorophyll a . Hence, our results do not support a major role of the phytoplankton community or aquatic bacteria on TEP concentrations and dynamics. This suggests a strong external control of TEP concentrations in boreal freshwaters, which can in turn affect particle dynamics and sedimentation in the recipient aquatic ecosystem.

Colored organic matter increases CO 2 in meso‐eutrophic lake water through altered light climate and acidity - Anna C. Nydahl; Marcus B. Wallin; Lars J. Tranvik; Carolin Hiller; Katrin Attermeyer; Julie A. Garrison; Fernando Chaguaceda; Kristin Scharnweber; Gesa A. Weyhenmeyer (Limnology and Oceanography, 2019)
Many surface waters across the boreal region are browning due to increased concentrations of colored allochthonous dissolved organic carbon (DOC). Browning may stimulate heterotrophic metabolism, may have a shading effect constraining primary production, and may acidify the water leading to decreased pH with a subsequent shift in the carbonate system. All these effects are expected to result in increased lake water carbon dioxide (CO 2 ) concentrations. We tested here these expectations by assessing the effects of both altered allochthonous DOC input and light conditions through shading on lake water CO 2 concentrations. We used two mesocosm experiments with water from the meso‐eutrophic Lake Erken, Sweden, to determine the relative importance of bacterial activities, primary production, and shifts in the carbonate system on CO 2 concentrations. We found that DOC addition and shading resulted in a significant increase in partial pressure of CO 2 ( p CO 2 ) in all mesocosms. Surprisingly, there was no relationship between bacterial activities and p CO 2 . Instead the experimental reduction of light by DOC and/or shading decreased the photosynthesis to respiration ratio leading to increased p CO 2 . Another driving force behind the observed pC O 2 increase was a significant decrease in pH, caused by a decline in photosynthesis and the input of acidic DOC. Considering that colored allochthonous DOC may increase in a warmer and wetter climate, our results could also apply for whole lake ecosystems and p CO 2 may increase in many lakes through a reduction in the rate of photosynthesis and decreased pH.

Unraveling the size‐dependent optical properties of dissolved organic matter - Urban J. Wünsch; Colin A. Stedmon; Lars J. Tranvik; François Guillemette (Limnology and Oceanography, 2018)
The size‐dependent optical properties of dissolved organic matter (DOM) from four Swedish lakes were investigated using High Performance Size Exclusion Chromatography (HPSEC) in conjunction with online characterization of absorbance (240–600 nm) and fluorescence (excitation: 275 nm, emission: 300–600 nm). The molecular size of chromophoric DOM (CDOM) was consistently higher than that of fluorescent DOM (FDOM), with an average difference of 0.37 kDa. The relative abundance of FDOM vs. CDOM ranged from 0.3 to 0.7 across lakes, and increased with decreasing average molecular size. Across sites, the CDOM spectral slopes of the large molecular size fraction were highly similar while the low molecular size fraction differed and contributed to different bulk spectral slopes. Our results indicate structural congruence of high molecular size DOM across systems while lake trophic status determined the characteristics of the low size range. Furthermore, the combination of HPSEC and parallel factor analysis (HPSEC‐PARAFAC2) allowed the decomposition of DOM fluorescence chromatograms. Three humic‐like components and one protein‐like component with broadly overlapping molecular size distributions were identified. This overlap provides further evidence for the supramolecular assembly hypothesis since fluorophores, as revealed by PARAFAC2, occur in aggregates of overlapping molecular size. Our results further suggest a link between the molecular size of these fluorophores and the associated supramolecular assemblies. This study demonstrates the potential for HPSEC and novel mathematical approaches to provide unprecedented insights into the relationship between optical and chemical properties of DOM in aquatic systems.

Sensitivity of freshwaters to browning in response to future climate change - Gesa A. Weyhenmeyer; Roger A. Müller; Maria Norman; Lars J. Tranvik (Climatic Change, 2016)

Absence of a priming effect on dissolved organic carbon degradation in lake water - Núria Catalán; Anne M. Kellerman; Hannes Peter; Francesc Carmona; Lars J. Tranvik (Limnology and Oceanography, 2015)

Regional‐scale variation of dissolved organic carbon concentrations in Swedish lakes - David A. Seekell; Jean-François Lapierre; Michael L. Pace; Cristian Gudasz; Sebastian Sobek; Lars J. Tranvik (Limnology and Oceanography, 2014)
We assessed spatial variability in dissolved organic carbon (DOC) concentrations measured in nearly 2000 Swedish lakes. Inter‐lake variance peaked at two different scales, representing within‐region and between‐region variability. The variation between regions was greater than the variation among lakes within regions. We tested relationships between DOC and runoff, drainage ratio, and altitude for spatial heterogeneity using geographically weighted regression. Relationships varied geographically, but cluster analysis delineated two contiguous regions of similar relationships. Altitude had a significant inverse relationship with DOC in the highlands, and drainage ratio had a significant positive relationship with DOC in the lowlands. These heterogeneous relationships explained regional patterns in DOC concentrations. We conclude that regions, rather than individual lakes, are a key, emergent scale of spatial variability for DOC concentrations. This scale of variability reflects the intersection of environmental gradients (e.g., altitude) with spatially heterogeneous relationships (e.g., DOC—drainage ratio relationship). Regional‐scale structure in limnological patterns indicates that individual lakes are not independent from one another, but are emergent groups where DOC concentrations are a function of similar environmental patterns and processes.

Controls of dissolved organic matter quality: evidence from a large‐scale boreal lake survey - Dolly N. Kothawala; Colin A. Stedmon; Roger A. Müller; Gesa A. Weyhenmeyer; Stephan J. Köhler; Lars J. Tranvik (Global Change Biology, 2014)
Inland waters transport large amounts of dissolved organic matter ( DOM ) from terrestrial environments to the oceans, but DOM also reacts en route, with substantial water column losses by mineralization and sedimentation. For DOM transformations along the aquatic continuum, lakes play an important role as they retain waters in the landscape allowing for more time to alter DOM . We know DOM losses are significant at the global scale, yet little is known about how the reactivity of DOM varies across landscapes and climates. DOM reactivity is inherently linked to its chemical composition. We used fluorescence spectroscopy to explore DOM quality from 560 lakes distributed across Sweden and encompassed a wide climatic gradient typical of the boreal ecozone. Six fluorescence components were identified using parallel factor analysis ( PARAFAC ). The intensity and relative abundance of these components were analyzed in relation to lake chemistry, catchment, and climate characteristics. Land cover, particularly the percentage of water in the catchment, was a primary factor explaining variability in PARAFAC components. Likewise, lake water retention time influenced DOM quality. These results suggest that processes occurring in upstream water bodies, in addition to the lake itself, have a dominant influence on DOM quality. PARAFAC components with longer emission wavelengths, or red‐shifted components, were most reactive. In contrast, protein‐like components were most persistent within lakes. Generalized characteristics of PARAFAC components based on emission wavelength could ease future interpretation of fluorescence spectra. An important secondary influence on DOM quality was mean annual temperature, which ranged between −6.2 and +7.5 °C. These results suggest that DOM reactivity depends more heavily on the duration of time taken to pass through the landscape, rather than temperature. Projected increases in runoff in the boreal region may force lake DOM toward a higher overall amount and proportion of humic‐like substances.

Resistance and resilience of microbial communities – temporal and spatial insurance against perturbations - Didier L. Baho; Hannes Peter; Lars J. Tranvik (Environmental Microbiology, 2012)
Summary Bacteria play fundamental roles for many ecosystem processes; however, little empirical evidence is available on how environmental perturbations affect their composition and function. We investigated how spatial and temporal refuges affect the resistance and resilience of a freshwater bacterioplankton community upon a salinity pulse perturbation in continuous cultures. Attachment to a surface avoided the flushing out of cells and enabled re‐colonization of the liquid phase after the perturbation, hence serving as a temporal refuge. A spatial refuge was established by introduction of bacteria from an undisturbed reservoir upstream of the continuous culture vessel, acting analogous to a regional species pool in a metacommunity. The salinity pulse affected bacterial community composition and the rates of respiration and the pattern of potential substrate utilization as well as the correlation between composition and function. Compared with the no‐refuge treatment, the temporal refuge shortened return to pre‐perturbation conditions, indicating enhanced community resilience. Composition and function were less disturbed in the treatment providing a spatial refuge, suggesting higher resistance. Our results highlight that spatial and temporal dynamics in general and refuges in particular need to be considered for conceptual progress in how microbial metacommunities are shaped by perturbations.

Pronounced seasonal dynamics of freshwater chitinase genes and chitin processing - Sara Beier; Vani Mohit; Thijs J. G. Ettema; Örjan Östman; Lars J. Tranvik; Stefan Bertilsson (Environmental Microbiology, 2012)
Summary Seasonal variation in activity of enzymes involved in polymer degradation, including chitinases, has been observed previously in freshwater environments. However, it is not known whether the seasonal dynamics are due to shifts in the activity of bacteria already present, or shifts in community structure towards emergence or disappearance of chitinolytic organisms. We traced seasonal shifts in the chitinase gene assemblage in a temperate lake and linked these communities to variation in chitinase activity. Chitinase genes from 20 samples collected over a full yearly cycle were characterized by pyrosequencing. Pronounced temporal shifts in composition of the chitinase gene pool (beta diversity) occurred along with distinct shifts in richness (alpha diversity) as well as chitin processing. Changes in the chitinase gene pool correlated mainly with temperature, abundance of crustacean zooplankton and phytoplankton blooms. Also changes in the physical structure of the lake, e.g. stratification and mixing were associated with changes in the chitinolytic community, while differences were minor between surface and suboxic hypolimnetic water. The lake characteristics influencing the chitinolytic community are all linked to changes in organic particles and we suggest that seasonal changes in particle quality and availability foster microbial communities adapted to efficiently degrade them.

Reciprocal subsidies between freshwater and terrestrial ecosystems structure consumer resource dynamics - Pia Bartels; Julien Cucherousset; Kristin Steger; Peter Eklöv; Lars J. Tranvik; Helmut Hillebrand (Ecology, 2012)
Cross‐ecosystem movements of material and energy, particularly reciprocal resource fluxes across the freshwater–land interface, have received major attention. Freshwater ecosystems may receive higher amounts of subsidies (i.e., resources produced outside the focal ecosystem) than terrestrial ecosystems, potentially leading to increased secondary production in freshwaters. Here we used a meta‐analytic approach to quantify the magnitude and direction of subsidy inputs across the freshwater–land interface and to determine subsequent responses in recipient animals. Terrestrial and freshwater ecosystems differed in the magnitude of subsidies they received, with aquatic ecosystems generally receiving higher subsidies than terrestrial ecosystems. Surprisingly, and despite the large discrepancy in magnitude, the contribution of these subsidies to animal carbon inferred from stable isotope composition did not differ between freshwater and terrestrial ecosystems, likely due to the differences in subsidy quality. The contribution of allochthonous subsidies was highest to primary consumers and predators, suggesting that bottom‐up and top‐down effects may be affected considerably by the input of allochthonous resources. Future work on subsidies will profit from a food web dynamic approach including indirect trophic interactions and propagating effects.

Terrestrial subsidies to lake food webs: an experimental approach - Pia Bartels; Julien Cucherousset; Cristian Gudasz; Mats Jansson; Jan Karlsson; Lennart Persson; Katrin Premke; Anja Rubach; Kristin Steger; Lars J. Tranvik; Peter Eklöv (Oecologia, 2012)

Constrained microbial processing of allochthonous organic carbon in boreal lake sediments - Cristian Gudasz; David Bastviken; Katrin Premke; Kristin Steger; Lars J. Tranvik (Limnology and Oceanography, 2012)
We investigated sediment bacterial metabolism in eight lakes with different inputs of allochthonous and autochthonous organic carbon in south‐central Sweden. Sediment bacterial production, mineralization, and biomass were measured seasonally and along a lake depth gradient in lakes with different water and sediment characteristics. Sediment bacterial metabolism was primarily controlled by temperature but also by the quality and origin of organic carbon. Metabolism was positively correlated to measures of autochthonous influence on the sediment organic carbon, but did not show a similar increase with increasing input of allochthonous organic carbon. Hence, in contrast to what is currently known for the water column, increasing terrestrial organic carbon influence does not result in enhanced sediment bacterial metabolism. The role of allochthonous organic carbon as the main driver of sediment bacterial metabolism suggested so far is contrary to our findings. Meio‐ and macrobenthic invertebrate biomass were, at most, weakly correlated to bacterial metabolism and biomass, suggesting limited control of sediment bacteria by grazing. Bacterial metabolism in boreal lake sediments is constrained by low temperatures and by the recalcitrant nature of the dominant organic carbon, resulting in sediments being an effective sink of organic carbon.

Selective decay of terrestrial organic carbon during transport from land to sea - Gesa A. Weyhenmeyer; Mats Fröberg; Erik Karltun; Maria Khalili; Dolly Kothawala; Johan Temnerud; Lars J. Tranvik (Global Change Biology, 2012)
Numerous studies have estimated carbon exchanges at the land–atmosphere interface, more recently also including estimates at the freshwater–atmosphere interface. Less attention has been paid to lateral carbon fluxes, in particular to the fate of terrestrial carbon during transport from soils via surface waters to the sea. Using extensive datasets on soil, lake and river mouth chemistry of the boreal/hemiboreal region we determined organic carbon ( OC ) stocks of the O horizon from catchment soils, annual OC transports through more than 700 lakes ( OC lakeflux ) and the total annual OC transport at S weden's 53 river mouths ( OC seaflux ). We show here that a minimum of 0.03–0.87% yr −1 of the OC soil stocks need to be exported to lakes in order to sustain the annual OC lakeflux . Across S weden we estimated a total OC lakeflux of ~2.9 Mtonne yr −1 , which corresponds to ~10% of S weden's total terrestrial net ecosystem production, and it is over 50% higher than the total OC seaflux . The OC loss during transport to the sea follows a simple exponential decay with an OC half‐life of ~12 years. Water colour, a proxy often used for dissolved humic matter, is similarly lost exponentially but about twice as fast as OC . Thus, we found a selective loss of the coloured portion of soil‐derived OC during its transport through inland waters, prior to being discharged into the sea. The selective loss is water residence time dependent, resulting in that the faster the water flows through the landscape the less OC and colour is lost. We conclude that increases in runoff will result in less efficient losses of OC , and particularly of colour, if the time for OC transformations in the landscape shortens. Consequently, OC reaching the sea is likely to become more coloured, and less processed, which can have far‐reaching effects on biogeochemical cycles.

Microbial biomass and community composition in boreal lake sediments - Kristin Steger; Katrin Premke; Cristian Gudasz; Ingvar Sundh; Lars J. Tranvik (Limnology and Oceanography, 2011)
We used phospholipid fatty acids (PLFA) to determine microbial biomass and community structure in the sediments of eight boreal lakes with different loadings of allochthonous organic carbon and total phosphorus (TP) in the water during the course of a year. The total concentration of PLFA, an estimate of the microbial biomass, depended more on TP, a proxy for pelagic primary production, but not on dissolved organic carbon, a proxy for terrestrial organic carbon input. The composition of PLFAs varied considerably over time, demonstrating seasonal dynamics in microbial community composition. When PLFA profiles in all lakes and seasons are compared, community composition is more similar within season than within lakes.

Preface - Thorsten Blenckner; Tiina Nõges; Lars Tranvik; Kurt Pettersson; Rahmat Naddafi (Hydrobiologia, 2011)

Lakes and reservoirs as regulators of carbon cycling and climate - Lars J. Tranvik; John A. Downing; James B. Cotner; Steven A. Loiselle; Robert G. Striegl; Thomas J. Ballatore; Peter Dillon; Kerri Finlay; Kenneth Fortino; Lesley B. Knoll; Pirkko L. Kortelainen; Tiit Kutser; et al. (Limnology and Oceanography, 2009)
We explore the role of lakes in carbon cycling and global climate, examine the mechanisms influencing carbon pools and transformations in lakes, and discuss how the metabolism of carbon in the inland waters is likely to change in response to climate. Furthermore, we project changes as global climate change in the abundance and spatial distribution of lakes in the biosphere, and we revise the estimate for the global extent of carbon transformation in inland waters. This synthesis demonstrates that the global annual emissions of carbon dioxide from inland waters to the atmosphere are similar in magnitude to the carbon dioxide uptake by the oceans and that the global burial of organic carbon in inland water sediments exceeds organic carbon sequestration on the ocean floor. The role of inland waters in global carbon cycling and climate forcing may be changed by human activities, including construction of impoundments, which accumulate large amounts of carbon in sediments and emit large amounts of methane to the atmosphere. Methane emissions are also expected from lakes on melting permafrost. The synthesis presented here indicates that (1) inland waters constitute a significant component of the global carbon cycle, (2) their contribution to this cycle has significantly changed as a result of human activities, and (3) they will continue to change in response to future climate change causing decreased as well as increased abundance of lakes as well as increases in the number of aquatic impoundments.

Linking allochthonous dissolved organic matter and boreal lake sediment carbon sequestration: The role of light‐mediated flocculation - Eddie von Wachenfeldt; Sebastian Sobek; David Bastviken; Lars J. Tranvik (Limnology and Oceanography, 2008)
We measured flocculation of dissolved organic carbon (DOC) in the water from a humic lake (DOC = 14.9 mg C L ‐1 ) and from an adjacent mire (DOC = 25.7 mg C L ‐1 ), in in situ enclosure experiments with different light regimes. Light stimulated the formation of organic particles in both waters, and organic particle formation was observed at all incubation depths, even in the dark controls. Production of phytoplankton biomass was negligible, and allochthonous DOC was the most important precursor of the sinking particles. 8‐22% and 25‐ 60% of the loss of DOC in lake and mire water, respectively, could be accounted for by flocculation. Depthintegrated flocculation based on the enclosure experiments was 14.7 mg C m ‐2 d ‐1 . Lake‐water DOC concentration and water color has been increasing during the last decade, and sediment trap studies show that gross sedimentation of organic carbon also increased. Thus flocculation of allochthonous DOC, stimulated by light, constitutes a pathway for the sequestration of carbon in lake sediments.

Sedimentation in Boreal Lakes—The Role of Flocculation of Allochthonous Dissolved Organic Matter in the Water Column - Eddie von Wachenfeldt; Lars J. Tranvik (Ecosystems, 2008)

Patterns and regulation of dissolved organic carbon: An analysis of 7,500 widely distributed lakes - Sebastian Sobek; Lars J. Tranvik; Yves T. Prairie; Pirkko Kortelainen; Jonathan J. Cole (Limnology and Oceanography, 2007)
Dissolved organic carbon (DOC) is a key parameter in lakes that can affect numerous features, including microbial metabolism, light climate, acidity, and primary production. In an attempt to understand the factors that regulate DOC in lakes, we assembled a large database (7,514 lakes from 6 continents) of DOC concentrations and other parameters that characterize the conditions in the lakes, the catchment, the soil, and the climate. DOC concentrations were in the range 0.1–332 mg L −1 , and the median was 5.71 mg L −1 . A partial least squares regression explained 48% of the variability in lake DOC and showed that altitude, mean annual runoff, and precipitation were negatively correlated with lake DOC, while conductivity, soil carbon density, and soil C:N ratio were positively related with lake DOC. A multiple linear regression using altitude, mean annual runoff, and soil carbon density as predictors explained 40% of the variability in lake DOC. While lake area and drainage ratio (catchment : lake area) were not correlated to lake DOC in the global data set, these two factors explained significant variation of the residuals of the multiple linear regression model in several regional subsets of data. These results suggest a hierarchical regulation of DOC in lakes, where climatic and topographic characteristics set the possible range of DOC concentrations of a certain region, and catchment and lake properties then regulate the DOC concentration in each individual lake.

Changes in bacterial community composition along a solar radiation gradient in humic waters - Silke Langenheder; Sebastian Sobek; Lars J. Tranvik (Aquatic Sciences, 2006)

Iron Constraints on Planktonic Primary Production in Oligotrophic Lakes - Tobias Vrede; Lars J. Tranvik (Ecosystems, 2006)

Using Satellite Remote Sensing to Estimate the Colored Dissolved Organic Matter Absorption Coefficient in Lakes - Tiit Kutser; Donald C. Pierson; Lars Tranvik; Anu Reinart; Sebastian Sobek; Kari Kallio (Ecosystems, 2005)

Weak coupling between community composition and functioning of aquatic bacteria - Silke Langenheder; Eva S. Lindström; Lars J. Tranvik (Limnology and Oceanography, 2005)
We performed a batch culture experiment with a factorial design in which sterile water from four lakes and bacterial assemblages (size‐fractionated lake water) from the same lakes were set up in all possible combinations. The functional performance (biomass yield, respiration, growth rates, and growth efficiency) of bacterial communities growing in the cultures depended primarily on the type of the medium and to a much lesser extent on the origin of the bacterial assemblage. Functional changes were only partly paralleled by changes in community composition, as indicated by terminal restriction fragment length polymorphism analysis. Similar bacterial communities developed in different cultures as a result of receiving either the same medium or the same inoculum, indicating that bacterial communities are comprised of populations of generalists that can grow under most conditions as well as populations with the life strategy of specialists. However, bacteria originating from a slightly acidic polyhumic lake failed to grow, grew unsteadily, or exhibited an extended lag phase when exposed to media originating from other lakes, indicating that the bacterial community in the polyhumic lake was not able to adapt rapidly to changes in environmental conditions.

Abundance and functions of natural organic matter species in soil and water - Lars J. Tranvik; Patrick A. W. van Hees; Ulla S. Lundstrm (Aquatic Sciences, 2004)

Degradation of dissolved organic matter in oxic and anoxic lake water - David Bastviken; Linn Persson; Göran Odham; Lars Tranvik (Limnology and Oceanography, 2004)
Decades of conflicting results have fueled a debate about how O 2 affects organic matter (OM) degradation and carbon cycling. In a laboratory study, using both OM taken directly from a humic lake and chemically isolated fulvic acid, we monitored the mineralization of dissolved OM in freshwater under purely oxic and anoxic conditions, under oxic then anoxic conditions, and under anoxic then oxic conditions, for 426 d. Between 5% and 24% of the initial OM was mineralized, with most extensive mineralization occurring under purely oxic and anoxic—oxic conditions. A sequential change in the O 2 regime did not result in greater overall degradation, but initially anoxic conditions favored subsequent oxic mineralization. A substantially greater fraction of the OM was degraded than in previous shorter studies, with as much as 50% of the total OM degradation occurring after 147 d into the experiment. Three fractions of the degradable OM were identified: OM degraded only under oxic conditions (68–78%), OM degraded more rapidly under anoxic conditions than under oxic conditions (16–18%), and OM degraded at equal rates under both oxic and anoxic conditions (6–14%). The degradation patterns of natural dissolved OM from a humic lake and chemically isolated fulvic acid were very similar, which indicates a similar level of bioavailability. The difference between anoxic and oxic degradation was greater in our long‐term studies than in previous short‐term experiments, which indicates that the oxic and anoxic degradation potentials vary with increasing overall OM recalcitrance and that similar oxic and anoxic degradation rates can be expected in short‐term experiments in which

Role of lakes for organic carbon cycling in the boreal zone - Grete Algesten; Sebastian Sobek; Ann‐Kristin Bergström; Anneli Ågren; Lars J. Tranvik; Mats Jansson (Global Change Biology, 2004)
We calculated the carbon loss (mineralization plus sedimentation) and net CO 2 escape to the atmosphere for 79 536 lakes and total running water in 21 major Scandinavian catchments (size range 437–48 263 km 2 ). Between 30% and 80% of the total organic carbon that entered the freshwater ecosystems was lost in lakes. Mineralization in lakes and subsequent CO 2 emission to the atmosphere was by far the most important carbon loss process. The withdrawal capacity of lakes on the catchment scale was closely correlated to the mean residence time of surface water in the catchment, and to some extent to the annual mean temperature represented by latitude. This result implies that variation of the hydrology can be a more important determinant of CO 2 emission from lakes than temperature fluctuations. Mineralization of terrestrially derived organic carbon in lakes is an important regulator of organic carbon export to the sea and may affect the net exchange of CO 2 between the atmosphere and the boreal landscape.

Food webs in sub-Antarctic lakes: a stable isotope approach - Lars-Anders Hansson; Lars J. Tranvik (Polar Biology, 2003)

Photochemical effects on the interaction of enzymes and dissolved organic matter in natural waters - Norman M. Scully; Lars J. Tranvik; William J. Cooper (Limnology and Oceanography, 2003)
Extracellular enzymes such as phosphatase (P ase ) and glucosidase (G ase ) can be inactivated in natural waters through photochemical processes. In this study, we examined the mechanisms involved in enzyme inactivation. We first explored the possibility of direct photoinactivation. The quantum yield spectrum (Φ Λ ) for the direct photoinactivation of P ase increased exponentially with decreasing wavelength, with a much steeper slope relative to other Φ Λ . This, combined with modeled half‐life values for direct photoinactivation in excess of 5 d, indicates that direct photoinactivation of P ase by natural sunlight in lakes is negligible. Nonetheless, photoinactivation of enzymes occurred rapidly in light‐exposed natural waters and suggested an indirect mechanism. The pH of natural waters greatly affected photoinactivation. In acid humic lake water exposed to ultraviolet radiation, the half‐lives of both P ase and G ase were 4 h. The half‐life of these enzymes under the same conditions were twofold higher for lake waters obtained from a limed humic lake (8 h). The higher rate of inactivation in acid water was likely caused by a pH‐mediated increase in Fe photoreduction and enzyme binding. Solutions of P ase with Fe(II) and H 2 O 2 resulted in rapid inactivation (half‐life 7 min at 8.9 µmol L −1 Fe). There was no significant inactivation of controls without H 2 O 2 , indicating that enzymes are inactivated through Fe(III)/enzyme binding, which is enabled through the oxidation of Fe(II) by H2O2 to Fe(III). Direct inactivation by reactive oxygen species (ROS) was ruled out by tests with ROS scavengers.

The catchment and climate regulation of pCO 2 in boreal lakes - SEBASTIAN SOBEK; GRETE ALGESTEN; ANN‐KRISTIN BERGSTRÖM; MATS JANSSON; LARS J. TRANVIK (Global Change Biology, 2003)
The regulation of surface water pCO 2 was studied in a set of 33 unproductive boreal lakes of different humic content, situated along a latitudinal gradient (57°N to 64°N) in Sweden. The lakes were sampled four times during one year, and analyzed on a wide variety of water chemistry parameters. With only one exception, all lakes were supersaturated with CO 2 with respect to the atmosphere at all sampling occasions. pCO 2 was closely related to the DOC concentration in lakes, which in turn was mainly regulated by catchment characteristics. This pattern was similar along the latitudinal gradient and at different seasons of the year, indicating that it is valid for a variety of climatic conditions within the boreal forest zone. We suggest that landscape characteristics determine the accumulation and subsequent supply of allochthonous organic matter from boreal catchments to lakes, which in turn results in boreal lakes becoming net sources of atmospheric CO 2 .

Contrasting effects of solar UV radiation on dissolved organic sources for bacterial growth - Lars J. Tranvik; Stefan Bertilsson (Ecology Letters, 2001)
The photochemical transformation of dissolved organic matter (DOM) in lakes and oceans has been shown to either reduce or enhance bacterial utilization. We compared the effects of UV radiation on the bacterial use of DOM in a wide range of lakes. Although complex DOM was converted in all irradiated samples into carboxylic acids that are readily utilized by bacteria, irradiation in several lakes resulted in a decreased ability of DOM to support bacterial growth. The effect of irradiation on the ability of DOM to promote bacterial growth was a positive function of the terrestrial humic matter, and a negative function of indigenous algal production. We suggest that the net effect of irradiation is a result of counteracting but concurrent processes rendering DOM either labile or recalcitrant. Humic DOM is predominantly transformed into forms of increased lability, whereas photochemical transformation into compounds of decreased bacterial substrate quality dominates in algal‐derived DOM. Hence, solar‐induced photochemical reactions interact with microbial degraders in different ways, depending on the origin and nature of the organic matter, affecting the transfer of energy within aquatic food webs, as well as the degradation and preservation of detrital organic matter, in different directions.

The effects of shredding invertebrates on the transfer of organic carbon from littoral leaf litter to water-column bacteria - Irene M. Bohman; Lars J. Tranvik (Aquatic Ecology, 2001)

Bioavailability and sources of DOC and DON in macrophyte stands of a tropical coastal lake - Ram nas Stepanauskas; Vinicius F. Farjalla; Lars. J. Tranvik; Jonas M. Svensson; Francisco A. Esteves; Wilhelm Granéli (Hydrobiologia, 2000)

Photochemical transformation of dissolved organic matter in lakes - Stefan Bertilsson; Lars J. Tranvik (Limnology and Oceanography, 2000)
In a survey of photochemical transformation of dissolved organic matter (DOM) in lake water, we found photochemical production of dissolved inorganic carbon (DIC) and low molecular weight carboxylic acids (oxalic, malonic, formic, and acetic acid), upon simulated solar ultraviolet (UV) radiation exposure of filter‐sterilized surface water from 38 investigated lakes. Given the large variability in water chemistry of the studied systems, we suggest that these photoproducts are universally produced in sunlight exposed lake water. The measured production of carboxylic acid carbon corresponded to 34.4% (median) of the produced DIC. The production of DIC and carboxylic acids during 8 h of mild UV irradiation corresponded to an average of 4.7% (SD 2.9) of the total dissolved organic carbon pool. Hence, photochemical degradation could be a major sink for DOM in the surface layer of lakes. All photoreaction rates were strongly correlated to the total radiation absorbed during UV exposure ( r s 2 > 0.8), which depends mainly on amount of colored DOM in the water. The variability in DIC production after normalizing for absorbed radiation energy could partly be attributed to general water chemistry parameters (e.g., pH, iron concentration, conductivity).

Bioavailability of wetland‐derived DON to freshwater and marine bacterioplankton - Ramūnas Stepanauskas; Lars Leonardson; Lars J. Tranvik (Limnology and Oceanography, 1999)
Access to bioavailable nitrogen often limits primary production in marine and freshwater ecosystems. Around 70% of nitrogen transported by rivers worldwide consists of dissolved organic nitrogen (DON), but its bioavailability has been poorly investigated. To assess the potential bacterial growth on DON, we developed a bioassay employing natural DON and bacterial inocula in medium manipulated to make N the limiting nutrient. We analyzed the bacterial utilization of the high‐molecular‐weight fraction of DON isolated by ultrafiltration from three wetlands in South Sweden throughout the year. The bioavailability of low‐molecular‐weight and bulk DON was also analyzed in one of the wetlands, where inorganic nitrogen concentration was sufficiently low and did not interfere with bioassays. The bioavailability of bulk DON in the latter wetland varied from 2% to 16%, suggesting that DON is an important nitrogen source for the biota of coastal waters. DON may be the dominant input of bioavailable nitrogen during summer, when nitrate concentrations in rivers decrease and DON bioavailability increases. Marine bacterioplankton assimilated a substantially larger fraction of DON than did freshwater bacterioplankton, on average by a factor of 2.4. This finding indicates that the susceptibility of DON to bacterial mineralization increases as it is transported from freshwaters into saline environments.

Rapid fluorometric assay of bacterial density in lake water and seawater - Lars J. Tranvik (Limnology and Oceanography, 1997)
This paper describes a rapid fluorometric method for the determination of bacterial densities ranging from 10 5 to 10 7 ml −1 by using the double‐stranded DNA stain PicoGreen. Reagents are added to water samples (200 µ l) without concentration of the bacteria or laborious extraction of bacterial DNA. The method works well both in lake water, including humic water with high background fluorescence, and in seawater. The PicoGreen assay successfully replaces time‐consuming microscopy for counts of bacterial cultures and can be used in natural water samples as well. In samples from 12 lakes representing a wide range of bacterial and algal concentrations, DNA content was closely correlated with bacterial numbers ( r = 0.96).